2022
DOI: 10.3389/fcimb.2022.814307
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Linked Kinase Reduces H3K9 Trimethylation to Enhance Herpes Simplex Virus 1 Replication

Abstract: Histone modifications control the lytic gene expression of herpes simplex virus 1 (HSV-1). The heterochromatin mark, trimethylation of histone H3 on lysine (K) 9 (H3K9me3), is detected on HSV-1 genomes at early phases of infection to repress viral gene transcription. However, the components and mechanisms involved in the process are mostly unknown. Integrin-linked kinase (ILK) is activated by PI3K to phosphorylate Akt and promote several RNA virus infections. Akt has been shown to enhance HSV-1 infection, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…A similar mechanism of HCMV restriction has emerged, where KAP1-associated SPOC1 impaired HCMV replication by binding to the HCMV major immediate-early promoter (MIEP) and subsequently recruiting other heterochromatin-building factors [ 70 ]. Herpesviruses such as EBV, KSHV, and HSV1 have all been shown to be restricted by KAP1 via H3K9me3 deposition [ 71 , 72 , 73 , 74 ]. In KSHV, it has been reported that the latency-associated nuclear antigen (LANA) mediates KAP1 recruitment to the ORF50 promoter, resulting in repressive epigenetic modifications by decreasing activating histone acetylation (AcH3), possibly through recruitment of the histone deacetylase complexes HDACs 1 and 2 [ 75 ].…”
Section: Virus Epigenetic Restriction Factors (Erfs)mentioning
confidence: 99%
“…A similar mechanism of HCMV restriction has emerged, where KAP1-associated SPOC1 impaired HCMV replication by binding to the HCMV major immediate-early promoter (MIEP) and subsequently recruiting other heterochromatin-building factors [ 70 ]. Herpesviruses such as EBV, KSHV, and HSV1 have all been shown to be restricted by KAP1 via H3K9me3 deposition [ 71 , 72 , 73 , 74 ]. In KSHV, it has been reported that the latency-associated nuclear antigen (LANA) mediates KAP1 recruitment to the ORF50 promoter, resulting in repressive epigenetic modifications by decreasing activating histone acetylation (AcH3), possibly through recruitment of the histone deacetylase complexes HDACs 1 and 2 [ 75 ].…”
Section: Virus Epigenetic Restriction Factors (Erfs)mentioning
confidence: 99%
“…ILK inhibition was associated with improved viability in mouse cardiomyocytes infected with coxsackievirus B3, the latter of which is the most common agent in viral myocarditis [17]. ILK was also shown to promote herpes simplex virus 1 (HSV-1) replication via the phosphorylation of Akt [18].…”
Section: Canonical Pathwaysmentioning
confidence: 99%
“…Accordingly, ILK plays a vital role in regulating various cellular processes, even virus infection. Currently, although it has been revealed that ILK participates in RNA and DNA virus infection [30][31][32], its role in DENV infection has not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%